2019
DOI: 10.1111/corg.12281
|View full text |Cite
|
Sign up to set email alerts
|

Initial public offering valuation and prior shared experience in the boardroom of threshold ventures: A study of industry effects

Abstract: Research question/issue We explore the following question: How do initial public offering (IPO) investors value the existence of prior shared experience (PSE) between the CEO and the board of threshold ventures? Research findings/insights Building on the resource provision role of the board, signaling, and the dynamics of decision making within teams literatures, our results show that extensive PSE between the CEO and the board is detrimental to IPO valuation because it augments the perceived risk of overconfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 142 publications
(312 reference statements)
0
4
0
Order By: Relevance
“…However, other scholars presented some contradictory results, showing that human capital sometimes has a dark side. For example, Pérez-Calero et al (2019) find that firms obtain lower valuations at IPO when their CEOs have previous shared work experience with board members, especially if they are in the same industry as the focal firm, as prospective investors perceive a higher risk of overconfidence and myopic decisions. Building on agency and resource dependence theories, Bertoni et al (2022) document an inverted U-shape relationship between the value of initial public offerings and the extent of board independence.…”
Section: Characteristics Of the Entrepreneurial/ Management Teammentioning
confidence: 99%
“…However, other scholars presented some contradictory results, showing that human capital sometimes has a dark side. For example, Pérez-Calero et al (2019) find that firms obtain lower valuations at IPO when their CEOs have previous shared work experience with board members, especially if they are in the same industry as the focal firm, as prospective investors perceive a higher risk of overconfidence and myopic decisions. Building on agency and resource dependence theories, Bertoni et al (2022) document an inverted U-shape relationship between the value of initial public offerings and the extent of board independence.…”
Section: Characteristics Of the Entrepreneurial/ Management Teammentioning
confidence: 99%
“…Veltrop et al (2017) underline that directors' financial expertise positively impacts their social status and conformity within the board, while directors' industry-specific expertise does not. Moreover, Pérez-Calero et al (2019) show that the diversity of experience between the CEO and the board mitigates the relationship between the extensiveness of prior shared experience and IPO valuation.…”
Section: Board Diversity As Moderating Variablementioning
confidence: 94%
“…The international scope of corporate governance research is indicated by the diverse set of governance environments studied in recent CGIR articles that include Australia, Canada, China, Germany, India, Indonesia, Iran, Italy, Japan, Korea, Russia, Spain, Sweden, Taiwan, the United Kingdom, the United States, and Vietnam, as well as multicountry studies (e.g., Deloof, Du, & Vanacker, 2020; Desender, LópezPuertas‐Lamy, Pattitoni, & Petracci, 2020; García‐Sánchez & García‐Meca, 2018; Lazzarini & Musacchio, 2018; Qian, Cao, & Cao, 2018; Tribó, 2019; Zhou & Guillén, 2019). Corporate governance research is by no means restricted to the average publicly held corporation but also deals with the unique challenges associated with specific types of firms like, for instance, audit firms (La Rosa, Caserio, & Bernini, 2019), banks (Sheedy & Griffin, 2018), business groups (Shin, Hyun, Oh, & Yang, 2018), closely held firms (Russino, Picone, & Dagnino, 2019), declining firms (Abebe & Tangpong, 2018), entrepreneurial ventures (Pérez‐Calero, Larrañeta, & Wright, 2019), family firms (Yeh & Liao, 2019), foundations (Thomsen, Poulsen, Børsting, & Kuhn, 2018), institutional investors (Semenova & Hassel, 2019), intergovernmental organizations (Federo & Saz‐Carranza, 2018), initial public offerings (IPOs) (González, Guzmán, Tellez‐Falla, & Trujillo, 2019), as well as state‐owned enterprises (Apriliyanti & Randøy, 2019). This research intensity demonstrates the spread of corporate governance studies in multiple disciplines but also leads to higher levels of fragmentation of the field.…”
Section: Introductionmentioning
confidence: 99%
“…. Corporate governance research is by no means restricted to the average publicly held corporation but also deals with the unique challenges associated with specific types of firms like, for instance, audit firms (La Rosa, Caserio, & Bernini, 2019), banks (Sheedy & Griffin, 2018), business groups (Shin, Hyun, Oh, & Yang, 2018), closely held firms (Russino, Picone, & Dagnino, 2019), declining firms (Abebe & Tangpong, 2018), entrepreneurial ventures (Pérez-Calero, Larrañeta, & Wright, 2019), family firms (Yeh & Liao, 2019), foundations (Thomsen, Poulsen, Børsting, & Kuhn, 2018), institutional investors (Semenova & Hassel, 2019), intergovernmental organizations (Federo & Saz-Carranza, 2018), initial public offerings (IPOs) (González, Guzmán, Tellez-Falla, & Trujillo, 2019), as well as state-owned enterprises (Apriliyanti & Randøy, 2019). This research intensity demonstrates the spread of corporate governance studies in multiple disciplines but also leads to higher levels of fragmentation of the field.…”
mentioning
confidence: 99%